2018
DOI: 10.1007/s00330-018-5626-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shift imaging for evaluation of adrenal masses: a systematic review and meta-analysis

Abstract: • Inclusion of CSI in abdominal MRI protocols provides an effective solution for classifying adrenal masses discovered on MR exams • Visual evaluation of adrenal CSI is sufficient; use of quantitative indices does not improve diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 40 publications
0
23
1
1
Order By: Relevance
“…MRI with chemical shift imaging should only be the first choice where CT is less desirable, for example during pregnancy, in children, or for patients with allergies to iodinated contrast (this is not an issue in noncontrast scans) ( 307 ). The use of chemical shift MRI to detect intracellular fat within lipid-rich adrenal adenomas and differentiate these from other lesions was first described in 1992 ( 310 ) ( Fig. 7 ).…”
Section: Imaging Evaluation Of An Aimentioning
confidence: 99%
See 1 more Smart Citation
“…MRI with chemical shift imaging should only be the first choice where CT is less desirable, for example during pregnancy, in children, or for patients with allergies to iodinated contrast (this is not an issue in noncontrast scans) ( 307 ). The use of chemical shift MRI to detect intracellular fat within lipid-rich adrenal adenomas and differentiate these from other lesions was first described in 1992 ( 310 ) ( Fig. 7 ).…”
Section: Imaging Evaluation Of An Aimentioning
confidence: 99%
“…There are both qualitative (visual analysis) and quantitative methods of imaging evaluation which involve assessing change in signal intensity of adrenal lesions between in-phase and out-of-phase sequences ( 309 ). A recent systematic review and meta-analysis reported that visual analysis and quantitative analysis of adrenal signal intensity index and adrenal-to-spleen ratio all have high accuracy for lipid-rich adenoma detection (95-98%), and diagnostic performance is not significantly improved by adrenal signal intensity index or the adrenal-to-spleen ratio ( 310 ). Consequently, if AIs are detected on MRI and findings are unambiguous for a benign lipid-rich adenoma further imaging may not be warranted.…”
Section: Imaging Evaluation Of An Aimentioning
confidence: 99%
“…Attenuation characteristics by Hounsfield Unit (HU) of adrenal masses are generally accepted to differentiate adenomas from non-adenomas masses. Nevertheless, CT and MRI scanning cannot distinguish between adenomas with and without hormone secretion (15, 16, 17). Hence, in addition to the imaging findings, endocrinologic assessment of the adrenal masses is necessary as well as the issue of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the preferred imaging method for evaluating the adrenal gland is CT, MRI can be performed in some patients due to some clinical advantages, such as the absence of radiation exposure. T1 and T2 weighted imaging can help in benign malignant separation, moreover, MR with chemical shift imaging method can be used for this purpose [ 20 ].…”
Section: Methodsmentioning
confidence: 99%